Development of Indonesian teaching materials based on thematic learning model to improve higher order thinking and numeracy literacy of elementary school students - Ritonga, Mara Untung; Wuryani, Elly Prihasti; Nasution, Rizki Fadila (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Improving Higher Order Thinking and numeracy literacy of elementary school students is indispensable in facing the challenges of 21st century education. The goal of this study is to Indonesian teaching materials based on a thematic learning model designed to strengthen these two skills in elementary school students. This study uses a research and development (R&D) approach with a 4-D model, namely Define, Design, Develop, and Disseminate. The subjects of this study include fourth grade students of SD Thomas Alva Edison Medan. The data collection method in the study uses questionnaires, questionnaires are used to analyze student needs, product validity tests by experts, and product trials. The analysis technique used in this study is quantitative descriptive. The results of the study show that the teaching materials developed are valid and effective, as evidenced by a percentage of 83% with a good category from material experts. The results of the validity test from teaching material design experts showed a percentage of 85% with a good category. The results of the validity test from linguists showed a percentage of 90% with a very good category. The results of the effectiveness test conducted in individuals and small groups showed that the percentage of effectiveness of individuals was 90% with the very good category and the small group was 94% with the very good category. This shows that the teaching materials developed have excellent effectiveness. The results of this study prove that Indonesian teaching materials designed with a thematic approach have great potential in supporting more integrated and contextual learning.